Communal Rhetoric: A Tool for Differentiation in Admission Processes into Education Communities in Israel (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
In the last few decades, the public education system has witnessed the establishment of new education communities, which offer a conceptual alternative to the traditional model of neighborhood schools. The term “Neighborhood School” defines an institution that caters to a population within a given geographical area, while the term “Education Community” expresses an ideological-value perception of supra-regional belonging that extends beyond the boundaries of space and local obligations.In this article I reveal a current paradox at the heart of registration and acceptance processes into these communities at the primary school level, and especially during the critical transition stage into the first grade. The existence of unique education communities is justified in the name of liberalism, pluralism, and containment; however, they activate discourse mechanisms that greenlight social isolation and aid in masking this exclusion. This phenomenon is mostly important for lively public debates on inequality in education and the creation of class-based privileges in public spaces in Israel.Based on the Politics of Recognition theory alongside sociological theories of social reproduction and implicit structural exclusion, data was gathered from 20 in-depth interviews with gatekeepers of the registration processes into education communities. The findings were produced using critical discourse analysis, and reveal three central themes: 1) A rhetoric conversion of the term “community” (the transition from physical perception to ideological perception); 2) A rhetoric of suitability that justifies segregation and separation; 3) Fear as a clear rhetorical method of self-censorship.In this study, I identify a continuum between Recognizing Communities and Differentiating Communities, and breakdown analytically the rhetorical masking mechanism that operates on three dimensions simultaneously: hidden from the regulator as an approved discourse of expectation management; concealed from applicants, seeing as the process is designed in a way that pushes them toward self-censorship; and hidden sometimes even from the gatekeepers themselves, who view the process as a pedagogical defense of the community. In my analysis, I show the liberal discourse of choice and autonomy is actively being used as a tool for the preservation of social inequality and the reinforcement of class-based privileges in public institutions.
Keywords: Choosing Education; Critical Discourse Analysis; Gentrification in Education; The Politics of Recognition; Segregated Community; Education Communities